HUBUNGAN ANTARA KOMPETENSI KEPRIBADIAN GURU DENGAN KARAKTER SISWA DI SMP MUHAMMADIYAH KOTA JAYAPURA PROVINSI PAPUA - Eka Trisna Putri Widyastuti; Yulius Mataputun; Diki Kurniawan; Meylani Aljeinie Tijow (NOKEN : Jurnal Pengelolaan Pendidikan, 2020)
This study aims to determine how the teacher's personality competence is, how the student's character is, and the relationship between teacher's personality competence and student character. The research subjects were class VIII students at SMP Muhammadiyah Jayapura with a population of 170 people and a sample of 119 people. Collecting data using a questionnaire and observation. Meanwhile, instrument analysis includes analysis of validity and reliability. The prerequisite test for data analysis included normality and linearity tests. Then the data analysis was carried out using the product moment correlation calculation and assisted by the Statistical Package for Science (SPSS) version 16. The results showed that the variable X teacher personality competence was in the very high category with a mean value of 146.56 which means that the teacher's personality competence was good. Then the student character Y variable is in the high category with a mean value of 131.72 which means that most of the students' characters are good. The calculation results show that rhitung is greater than rtable (0.544> 0.180). This value concludes that at a significant level of 0.05% there is a relationship between teacher personality competence and student character at SMP Muhammadiyah Jayapura. The findings of this study can be used as a reference for developing the implementation of Strengthening Character Education (PPK) in schools.Keywords: Teacher’s personality competencies; student’s characters